PERLINDUNGAN HUKUM TERHADAP KONSUMEN HOTEL BATIK YOGYAKARTA - M. Shidqon Prabowo (IAIN Syekh Nurjati Cirebon, 2019)
AbstractThis research is intended to explain the scientific study framework for legal writing, namely: first, to find out the legal protection measures for hotel service users/consumers provided by hotel business operators to Batik Hotel service users, in Yogyakarta. And second, to find out how the responsibility of Batik Hotel entrepreneurs towards Batik Hotel service users for lost items. This research has done at the one-star hotel which is located in the municipality of Yogyakarta explained the security assurance of goods and / or services in today's business world, in the form of quality of service either quality, security, and safety that are devoted to service users / consumers and entrepreneurs. The study was conducted at the Hotel Batik in the Yogyakarta Municipality and explained the legal protection carried out in the form of quality, security, and safety that is specific to service users/consumers and business people. In this study, the method used is Empires/Juridical Normative because it uses primary data as the main source, while the research specification is descriptive analysis in the method of collecting data through library data and field data to provide information that can support the process of this research. The results in this study, namely business operators (batik hotels) while serving consumers or users of batik hotel services, have provided maximum legal protection and the application of legal protection has been felt and expressed by batik hotel service users well.Keywords: Protection Law, Consumer, and Hotel. AbstrakPenelitian ini bertujan untuk menjelaskan kerangka studi ilmiah penulisan hukum, yaitu: pertama, untuk mengetahui upaya perlindungan hukum terhadap pengguna jasa hotel/konsumen yang diberikan oleh pelaku usaha hotel kepada pengguna jasa Hotel Batik, di Yogyakarta. Dan kedua, untuk mengetahui bagaimana tanggung jawab pengusaha Hotel Batik terhadap pengguna jasa Hotel Batik atas barang yang hilang. Penelitian dilakukan di Hotel Batik yang berada di kotamadya Yogyakarta dan menjabarkan mengenai perlindungan hukum yang dilakukan baik berupa mutu, keamanan, dan keselamatan yang dikhususkan kepada pengguna jasa/ konsumen dan pelaku usaha. Pada penelitian ini metode yang digunakan yaitu secara Emperis/Yuridis Normatif karena menggunakan data primer sebagai sumber utama, sedangkan sedangkan spesifikasi penelitian bersifat deskriptif analisis dalam metode pengumpulan data melalui data kepustakaan dan data lapangan untuk memberikan keterangan yang dapat mendukung terhadap proses penelitian ini. Adapun hasil dalam penelitian ini, yaitu pelaku usaha (hotel batik) selama melayani konsumen atau pengguna jasa hotel batik telah memberikan perlindungan hukum yang semaksimal mungkin dan penerapan perlindungan hukum telah dirasakan dan dinyatakan oleh pengguna jasa hotel batik secara baik.Kata Kunci: Perlindungan Hukum, Konsumen, dan Hotel.